New immunotherapeutic strategies for the treatment of neuroblastoma. (March 2015) - Croce, Michela; Corrias, Maria Valeria; Rigo, Valentina; Ferrini, Silvano
The prognosis of high-risk neuroblastoma (NB) is still poor, in spite of aggressive multimodal treatment. Recently, adjuvant immunotherapy with anti-GD2 antibodies combined with IL-2 or GM-CSF has been shown to improve survival. Several other immunotherapy strategies proved efficacy in preclinical models of NB, including different types of vaccines, adoptive cell therapies and combined approaches. The remarkable differences in the immunobiology of syngeneic models and human NB may, at least in part, limit the translation of preclinical therapies to a clinical setting. Nonetheless, several preliminary evidences suggest that new antibodies, cancer vaccines and adoptive transfer of lymphocytes, genetically engineered to acquire NB specificity, may result in clinical benefit, and clinical studies are currently ongoing.